Formas de la corporalidad en el pensamiento ilustrado entre España y América Latina - Morgan, Muriel (2021)
This work presents some insights around corporeality in the kingdoms of Spain during the Bourbon Reforms. These policies involved a substantial change in the government’s management, representation and handling of bodies. Intellectuals of the Spanish Enlightenment aimed to intervene on bodies to internalise an «ideal body type», tied to notions of robustness, skills, strength, manual labors and work discipline. We will focus on three paradigmatic intellectuals: Campomanes, Jovellanos and Cabarrús. Through specific mechanisms, tied to certain institutions, they proposed the interiorization of this prototype of ideal corporeality. We will argue that, from these authors point of view, mind and body had to be pragmatically nourished in order to mold useful citizens in terms of productivity.